Case Report: 18F-FDOPA PET in the clinical management of a dog with an intraventricular tumor suspected to be choroid plexus papilloma - Wang, Juwon; Chae, Yeon; Lee, Dohee; Yun, Taesik; Kim, Hakhyun; Kang, Byeong-Teck (Frontiers in Veterinary Science, 2025)
An 8-year-old neutered male Miniature Poodle, weighing 6.7 kg, was presented with lethargy, anorexia, and single seizure episode. Neurological examination revealed bilaterally absent menace reflexes and an obtunded mental status. Magnetic resonance imaging showed a papilliform shaped mass measuring 1.2 × 1.4 × 1.3 cm in size, with a volume of 1.17 cm3 in the third ventricle. 3,4-dihydroxy-6-[18F] fluoro-l-phenylalanine (18F-FDOPA) positron emission tomography/computed tomography (PET/CT) was performed 53 days after presentation, revealing a hypermetabolic region in the intraventricular mass with mean and maximal standardized uptake values (SUVmean and SUVmax) of 1.2 and 1.42, respectively, and a tumor to normal tissue (T/N) ratio of 1.33. The mass lesion measured 1.3 × 1.4 × 1.2 cm in size, with a volume of 1.09 cm3 on contrast-enhanced CT images. The metabolic tumor volume (MTV) was 1.184 cm.3 No evidence of brain parenchymal metastases was observed. Therefore, the dog was tentatively diagnosed with a brain tumor, which was suspected to be a choroid plexus papilloma (CPP) and chemotherapy with prednisolone and cyclophosphamide was initiated. As worsening clinical signs were observed, a second 18F-FDOPA PET/CT scan was performed on day 183. The SUVmean, SUVmax, and T/N ratio of the lesion were 1.49, 1.85, and 1.62, respectively. The mass lesion measured 1.0 × 1.0 × 1.3 cm in size, with a volume of 0.68 cm3 on contrast-enhanced CT images, whereas the MTV was increased to 2.217 cm3. The dog died 186 days after the presentation. To the best of our knowledge, this is the first report describing the 18F-FDOPA PET/CT findings in a dog with an intraventricular brain tumor suspected of having CPP. In the present case, although the lesion size decreased on CT contrast imaging, an increase in the MTV was observed on follow-up 18F-FDOPA PET/CT after chemotherapy. Thus, an increase in MTV post-chemotherapy combined with the worsening clinical signs and limited survival period in dogs correlates with poor prognosis, as previously reported in a human study. This case offers significant diagnostic insights into canine intraventricular tumors within the field of veterinary medicine.